National Environment Policy Instruments: how are they doing after 40 years of promulgation? (Research, Society and Development, 2022)
In the early twentieth century concern for the environment had a remedial character, the prevention only started to be considered only in the middle of the last century. Aimed a rational use of natural resources in the beginning of the 80's Brazil enactment of the Law number 6.938/81 that institutes the National Environment Policy this low also created the National Environment System. Focus exclusive on the rational use of natural resources, this Law brought: definitions, objectives and principles. However, establishing instruments for the implementation of this policy was the most daring and challenging proposal so far. Thus, thirteen instruments were established that would function as tools in the search for an economy based on sustainable economic development. The new Constitution of 1988, Complementary Laws Resolutions National Environment Council, Normative Instructions and Ministerial Decrees regulated these instruments. The current situation of all these devices was the argumentative basis that supported the position of this work. The need for updating, the fragile performance of the public authorities, and impunity in the face of conduct harmful are facts that compromise the action of these tools. It is noteworthy that, even after forty years, there is much to be done, mainly due to the dynamic character that involves the use of environmental resources.